Effect of Respiration and Vascular Tone on Heart Rate Variability in Rats - Chizh, Nikolay A. (Problems of Cryobiology and Cryomedicine, 2016)
Basing on findings of a combined study (electrocardiography, pneumotachography, direct sphygmography) the paper discusses the effect of respiration and vascular tone on heart rate variability (HRV) in rats and presents a physiological interpretation of the selected spectral ranges. Studying the HRV in conscious rats showed the lower HF-wave range limit to be not higher than 0.8 Hz, and the upper one not less than 2.5 Hz; under stress this index increased up to 3 Hz. The experiments showed that conscious rats were characterized with the ‘package-like’ respiration (from 2 to 15–20 s). The respiratory rate in each ‘package’ was different, therefore two or more peaks might be recorded at high-frequency spectral range. This fact confirmed the existence of several oscillators-pacemakers of respiratory center. In the anaesthetised rats the vasomotor waves were established to affect the variability of respiratory and heart rates within the range of 0.25–0.5 Hz with 0.4 Hz peak. Therefore the lower limit of the average MF waves should not exceed 0.25 Hz. Probl Cryobiol Cryomed 2016; 26(3): 260–270